PENINGKATAN EFEKTIFITAS PENJURUSAN MAHASISWA ILMU KOMPUTER MENGGUNAKAN OTOMATISASI PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING - Dona Yuliawati (Jurnal Informatika, 2013)
One of the determination the successful students in lectures is the appropriateness in the selection of the courses. In fact, many high school graduated were experiencing difficulty decide the course that will be chosen. In general they don’t know what program should be chosen after graduated from the high school. Unsuitable selection of courses is often experienced by college students perceived generally after undergo the lectures more than a semester. In many case, the student proposed to get to transfer the majors to other appropriate things. It will impact in low index achievement of the students, the length of the study even the occurrence of drop-out (DO). These problems might be solved by applying a system decision making development method of Simple Additive Weighting (SAW).Keyword : SPK, Drop Out, SAW(Simple Additive Weighting)